Personal protective measures and settings on the risk of SARS-COV-2 community transmission: a case–control study - Huguet-Torres, Aina; Castro-Sánchez, Enrique; Capitán-Moyano, Laura; Sánchez-Rodríguez, Cristian; Bennasar-Veny, Miquel; Yáñez, Aina M. (Frontiers in Public Health, 2024)
Background During the SARS-CoV-2 pandemic, nurses of primary health care has been an important role in Spain. Even so, the data obtained in the tracing have been scarcely used to investigate the possible mechanisms of transmission. Few studies focused on community transmission, evaluating the effectiveness of individual protective measures and exposure environment. The main aim of the study was to evaluate the association between individual protective measures and SARS-CoV-2 transmission in the community and to compare secondary attack rates in different exposure settings. Methods A case–control study from contact tracing of SARS-CoV-2 index patients. COVID-19 contact tracing was led by nurses at the COVID-19 Coordinating Centre in Majorca (Spain). During the systematic tracing, additional information for this study was collected from the index patient (social-demographic variables, symptoms, the number of close contacts). And also, the following variables from their close contacts: contact place, ventilation characteristics mask-wearing, type of mask, duration of contact, shortest distance, case-contact relationship, household members, and handwashing, the test result for SARS-CoV-2 diagnostic. Close contacts with a positive test for SARS-CoV-2 were classified as “cases” and those negative as “controls.” Results A total of 1,778 close contacts from 463 index patients were identified. No significant differences were observed between the sexes but between age groups. Overall Secondary Attack Rate (SAR) was 24.0% (95% CI: 22.0–26.0%), 36.9% (95% CI: 33.2–40.6%) in closed spaces without ventilation and 50.7% (95% CI: 45.6–55.8%) in exposure time > 24 h. A total of 49.2% of infections occurred among household members. Multivariate logistic regression analysis showed that open-air setting (OR 0.43, 95% CI: 0.27–0.71), exposure for less than 1 h (OR 0.19, 95% CI: 0.11–0.32), and wearing a mask (OR 0.49, 95% CI: 0.28–0.85) had a protective effect transmission of SARS-CoV-2 in the community. Conclusion Ventilation of the space, mask-wearing and shorter exposure time were associated with a lower risk of transmission in the community. The data obtained allowed an assessment of community transmission mechanisms and could have helped to improve and streamline tracing by identifying close contacts at higher risk.